2021
DOI: 10.1186/s41043-021-00230-5
|View full text |Cite
|
Sign up to set email alerts
|

High sodium food consumption pattern among Malaysian population

Abstract: Background Sodium is an essential mineral needed by the human body that must be obtained from food. An excess intake, however, can lead to many diseases. As food is the main source of sodium, this study aims to provide information on high sodium food consumption patterns in the Malaysian adult population. Methods The Malaysian Community Salt Study (MyCoSS) was a nationwide cross-sectional study, conducted between October 2017 and March 2018. A mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Our study showed a low frequency of self-care behaviour especially in reducing salt intake, which were consistent with another study which reported that 79% of respondents exceeded the recommended amounts set by local and international health guidelines [ 47 ]. Other nation-wide surveys reported that the mean sodium intake in Malaysians was higher than recommended [ 48 – 50 ]. Our study highlighted several barriers of reducing salt intake in the local population such as lack of time for food preparation, limited choices and used to the family diet.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a low frequency of self-care behaviour especially in reducing salt intake, which were consistent with another study which reported that 79% of respondents exceeded the recommended amounts set by local and international health guidelines [ 47 ]. Other nation-wide surveys reported that the mean sodium intake in Malaysians was higher than recommended [ 48 – 50 ]. Our study highlighted several barriers of reducing salt intake in the local population such as lack of time for food preparation, limited choices and used to the family diet.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that most of the participants agreed that the salt intake among Malaysians is high, as many food products including fast foods, snacks, processed foods, fermented foods and traditional foods, as well as food in the out-of-home sectors are high in salt content. The top ten food items that contributed to the highest sodium consumption among adult Malaysians include kolok mee, light soy sauce, curry noodle, vegetable with soy sauce/oyster sauce, fried instant noodle, noodle soup, vegetable with salted fish, fried vegetable, roti canai/ roti telur and fried rice [20]. Findings by the Singapore National Nutrition Survey 2018 showed that the use of seasoning, sauces and salt in food preparation make up three-quarters of salt consumed in the diet [21].…”
Section: Discussionmentioning
confidence: 99%
“…Fried noodles contained a high sodium content due to the ingredients used in the preparation stage. Fried noodles are often cooked with many sauces, especially soy sauce, thick soy sauce, oyster sauce, and chili sauce which contribute to high sodium content [ 30 , 31 , 32 ]. The sauces were added to add more flavor to the food and to make it more palatable to eat [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%